En torno al verbo incluir: Performatividades heurísticas de la educación inclusiva (2021)
us to recognize that it is more interested in shaping a program of change and justice. The work at first, analyzes the power of the epistemological nomadismin of inclusive education, which inaugurates a new way of conceiving and practicing heuristic work. Its eventual, transrelational, alterative and transformative nature of thought schemes describe it as a powerful resource and heuristic reasoning system for thinking about the constitutive problems of the contemporary world. In a second moment, the characteristics of the verb include as a vector of analysis and configutation of reality are analyzed, it articulates its activity through the notions of performativity and performance, revealing multiple forms of action and intervention of reality and space. So far, inclusive education can be described in terms of movement, especially when used in terms of slogans and, on occasions, to identify itself around a strange ideal of diversity. The work concludes by examining the potential of analytical constellations in the construction of knowledge of inclusive education